2016
DOI: 10.3391/ai.2016.11.4.04
|View full text |Cite
|
Sign up to set email alerts
|

The contemporary records of aquatic plants invasion through the Danubian floodplain corridor in Serbia

Abstract: In a recent article, Malaquias et al. (2016) use molecular tools to test the conspecificity of the aglajid sea slug Chelidonura fulvipunctata Baba, 1938 populations from two sites in the Mediterranean (Cyprus, Italy) and the Indo-West Pacific (Mozambique, Lizard Island, Australia, and Marshall Islands). The authors then postulate that the species has entered the Red Sea from the Mediterranean Sea through the Suez Canal, the latter acting as a "revolving door" that can allow species of Indo-Pacific origin to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This study has found significant differences in invasion levels between the studied catchment areas, highlighting the catchment areas of the Timok and Danube rivers as the most invaded overall. Such findings are consistent with other studies denoting the Danube as an important plant invasion corridor (Stevanović et al 2004;Paunović et al 2015;Anđelković et al 2016;Wagner et al 2020). The highly invaded Timok river catchment area, geographically a part of the Carpathian massive, seems to be experiencing a similar increase in invasion levels already observed in the Carpathian Mountains of Ukraine (Simpson and Prots 2013).…”
Section: Differences In Invasion Levels Across Catchment Areassupporting
confidence: 91%
“…This study has found significant differences in invasion levels between the studied catchment areas, highlighting the catchment areas of the Timok and Danube rivers as the most invaded overall. Such findings are consistent with other studies denoting the Danube as an important plant invasion corridor (Stevanović et al 2004;Paunović et al 2015;Anđelković et al 2016;Wagner et al 2020). The highly invaded Timok river catchment area, geographically a part of the Carpathian massive, seems to be experiencing a similar increase in invasion levels already observed in the Carpathian Mountains of Ukraine (Simpson and Prots 2013).…”
Section: Differences In Invasion Levels Across Catchment Areassupporting
confidence: 91%
“…A similar absence of E. nuttallii and isolated, scattered occurrences of E. canadensis in the Mediterranean biogeographical region of Italy was recorded by Buldrini et al [ 32 ] who suggest that E. nuttallii is the less thermophilous of the two. A survey from neighbouring Serbia [ 33 ] found that most waterweed records have been documented in surface running waters as opposed to standing waters. This is also the case in our survey, even though in other parts of Europe, waterweeds are commonly recorded and studied in lakes [ 6 , 10 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at 5 sampling sites, they were both recorded, but in different years, never accompanying one another. Over the years, E. nuttallii replaced E. canadensis in three reservoirs on the Drava River in Northern Croatia (sites number [33][34][35][36][37][38] and in two canals of the Drava River Basin (sites number 31,32,43,44). Overall, waterweeds were mostly recorded in rivers and canals (90% of records).…”
Section: Distributionmentioning
confidence: 99%
“…by competition/overgrowth) by A. filiculoides due to its greater adaptability to eutrophication caused by urbanisation and agricultural activities (Lastrucci et al 2019). Indeed, in Serbia, which borders Croatia through the River Danube, only A. filiculoides has been recognised as present in the aquatic systems of the region (Anđelković et al 2016). In addition, a survey performed in Czechia revealed that only A. filiculoides is present and that A. cristata has never occurred in the country (Pyšek et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The native distribution of C. caroliniana covers the eastern part of subtropical and temperate areas of South America (Roberts and Florentine 2022), hence matching current and projected climate conditions in both risk assessment areas (Beck et al 2018;Rodríguez-Merino et al 2018). This species is established in Serbia (Vojvodina, near the Croatian border), where it has expanded from Hungary probably through the canal network of the hydrosystem Danube-Tisa-Danube (Anđelković et al 2016). In Europe, C. caroliniana is still not regarded as invasive and is mostly found in localised and scattered populations (Roberts and Florentine 2022), though in The Netherlands, it has been declared as high risk (Matthews et al 2013).…”
Section: Discussionmentioning
confidence: 99%